Imagem Corporal & Intenções de Aleitamento Materno no 3º Trimestre da Gravidez - Sim-Sim, Margarida (2013)
Introduction: During pregnancy there are a varied number of changes that have significant effects in different body parts, as well as in the body as a whole. By the end of the third trimester, woman’s decision on the preferred method to nurture the child is eminent. Objectives: 1) describe the body-image of pregnant women and relate it with 2) the weeks of pregnancy, 3) the Body Mass Index [BMI] on the 3rd trimester, 4) the breastfeeding intentions and 5) the expectation of having nurses’ support. Method: Transversal, quantitative and descriptive study. Convenient sample of 47 women on their last trimester which attended a group of pre-natal class. The questionnaire includes sociodemografic aspects and variables related with body-image (i.e. Attitude Toward Body Image Scale; Strang & Sullivan, 1985), with α of Cronbach of.817, and with breastfeeding intentions (i.e. Infant Feeding Intentions; Nommsen-Rivers, & Dewey, 2009) with α of Cronbach of .687, as well as with the expectations of being supported by nurses. Results: The pregnant woman’s body-image is high (M=45; DP=8,29). We observe a significative correlation between this variable and the weeks of pregnancy (r=.460; p=.003). No association was verified between the body-image and the pregnant BMI, as well as in the intentions of breastfeeding until the sixth month. However, such occurs in the indicator that expresses the atempt of at least trying to breastfeed (r=.319; p=.039). The expectation of having the support of nurses in breastfeeding is related to body-image(r=.354; p=.021). Conclusions: The pregant BMI is not enhanced on the body-image. Though there doesn’t seem to exist a strong determination towards breastfeeding, having the support of nurses may improve the results of the attempts to breastfeed.